Mesenchymal stem/stromal cells enhance engraftment, vasculogenic and pro-angiogenic activities of endothelial colony forming cells in immunocompetent hosts. Issue 1 (December 2017) - Shafiee, Abbas; Patel, Jatin; Lee, James; Hutmacher, Dietmar; Fisk, Nicholas; Khosrotehrani, Kiarash
Abstract The clinical use of endothelial colony forming cells (ECFC) is hampered by their restricted engraftment. We aimed to assess engraftment, vasculogenic and pro-angiogenic activities of ECFC in immunocompetent (C57BL/6: WT) or immunodeficient (rag1 −/− C57BL/6: Rag1) mice. In addition, the impact of host immune system was investigated where ECFC were co-implanted with mesenchymal stem/stromal cells (MSC) from adult bone marrow (AdBM-MSC), fetal bone marrow (fBM-MSC), fetal placental (fPL-MSC), or maternal placental (MPL-MSC). Transplantation of ECFCs in Matrigel plugs resulted in less cell engraftment in WT mice compared to Rag1 mice. Co-implantation with different MSCs resulted in a significant increase in cell engraftment up to 9 fold in WT mice reaching levels of engraftment observed when using ECFCs alone in Rag1 mice but well below levels of engraftment with MSC-ECFC combination in Rag1 recipients. Furthermore, MSCs did not reduce murine splenic T cell proliferation in response to ECFCsin vitro . ECFCs enhanced the murine neo-vascularization through paracrine effect, but with no difference between Rag1 and WT mice. In conclusions, the host adaptive immune system affects the engraftment of ECFCs. MSC co-implantation improves ECFC engraftment and function even in immunocompetent hosts mostly through non-immune mechanisms.